Knowledge management as strategy for k-economy: Looking at Malaysia environment - Ibrahim, Amlus; Ismail, Hirun Azaman; Asree, Susita; Said, Mohd Radzai (2006)
The paper study on the knowledge management contribution in K-Economy.Every company faces the challenge of how to best manage its knowledge assets to generate value for the marketplace and obtain competitive advantage Such advantage derives from special capabilities that are rare, valuable, non substitutable, and costly to imitate Historically, the focus was on capabilities involving tangible assets, knowledge is widely recognized as the source for competitive advantage, with the tangible assets representing the physical manifestation of but a fraction of this knowledge As companies scramble to develop strategies for more proactively and strategically managing their knowledge, the field of Knowledge management (KM)receives increasing attention from trade organizations and academic journals.From this study it was found that to improve the chances of conclusively demonstrating value to the K-Economy, a new KM implementation in an innovation organization should address issues such as organization's goals and strategies, access tacit knowledge, provide search tools, promote creativity, capture new learning, and build a supportive culture,insufficient communication, failure to integrate knowledge, lack of time to learn ,lack of training .a senses there was little personal benefit in knowledge management.